2021
DOI: 10.3389/fphys.2021.706528
|View full text |Cite
|
Sign up to set email alerts
|

Rapalink-1 Increased Infarct Size in Early Cerebral Ischemia–Reperfusion With Increased Blood–Brain Barrier Disruption

Abstract: It has been reported that the mechanistic target of rapamycin (mTOR) pathway is involved in cerebral ischemia–reperfusion injury. One of the important pathological changes during reperfusion after cerebral ischemia is disruption of blood–brain barrier (BBB). Rapamycin, a first-generation mTOR inhibitor, produces divergent effects on neuronal survival and alteration in BBB disruption. In this study, we investigated how Rapalink-1, a third-generation mTOR inhibitor, would affect neuronal survival and BBB disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
(66 reference statements)
3
17
0
Order By: Relevance
“…Studies also showed that 44 can effectively impair the motility and clonogenicity of GBM stem cells and reduce the expression of stem cell molecules 94 . However, 44 has an effect on the aggravation of BBB disruption, which may lead to serious side effect 95 . The chemical structure of 44 and the mTOR co-crystallized with 44 are presented in Fig.…”
Section: Targets Of Gbm and Relevant Small-molecule Novel Therapeuticsmentioning
confidence: 99%
“…Studies also showed that 44 can effectively impair the motility and clonogenicity of GBM stem cells and reduce the expression of stem cell molecules 94 . However, 44 has an effect on the aggravation of BBB disruption, which may lead to serious side effect 95 . The chemical structure of 44 and the mTOR co-crystallized with 44 are presented in Fig.…”
Section: Targets Of Gbm and Relevant Small-molecule Novel Therapeuticsmentioning
confidence: 99%
“…Several studies have revealed a positive neuroprotective effect of mTORCs upregulation after cerebral ischemia [ 105 , 106 ]. In the tMCAo model, mTORC1 and mTORC2 activity suppression using Rapalink-1, a third-generation mTOR inhibitor, has been reported to exacerbate neuronal damage induced by ischemia in the short-term, worsen BBB stability, and increase the area of damage [ 107 ]. These observations suggest that the upregulation of mTORC activity after cerebral ischemia has beneficial effects on the CNS.…”
Section: Mtor After Cerebral Ischemiamentioning
confidence: 99%
“…Approval for this new indication could therefore take less time at a substantially reduced cost (Ashburn and Thor, 2004 ). Chi et al provide the first experimental stroke study of the mTOR inhibitor, Rapalink-1 (Chi et al, 2021 ). Rapalink-1 combines rapamycin with the mTOR kinase inhibitor, MLN0128 (molecular weight of Rapalink-1= 1,784 g/mol vs. rapamycin = 914 g/mol), with the goal of leveraging the high affinity of rapamycin for mTORC1 (via FK506 Binding Protein 12) to selectively deliver MLN0128 to the ATP-site of the mTORC1 complex (Rodrik-Outmezguine et al, 2016 ).…”
Section: Mtor Inhibitors In Ischemic Stroke Less May Be Morementioning
confidence: 99%
“…Given the increased potency of Rapalink-1, it would be expected that doses of Rapalink-1 needed for brain cytoprotection in stroke would be much lower than rapamycin (optimal dose for rapamycin <2 mg/kg). Chi et al used 2 mg/kg of Rapalink-1, which was associated with mTORC1 and mTORC2 inhibition and increased infarct volume (Chi et al, 2021 ). These findings further highlight the importance of mTORC2 signaling for cell survival during ischemia and suggest that although the dose of Rapalink-1 used is not too dissimilar to cytoprotective doses of rapamycin, the increased potency of Rapalink-1 may have resulted in mTORC2 inhibition at a lower dose.…”
Section: Mtor Inhibitors In Ischemic Stroke Less May Be Morementioning
confidence: 99%
See 1 more Smart Citation